Development and promotion strategies of pickleball in Jambi Province - Nurhaliza Nurhaliza; Endarman Saputra; Wawan Junresti Daya (Sriwijaya Journal of Sport, 2025)
Research Problems: Challenges such as limited facilities and the small number of active players are obstacles faced by the community in popularising this sport. Research Objectives: to identify the strategies that have been used by the pickleball community in Jambi in developing and promoting this sport. Methods: Using qualitative descriptive methods with a case study approach. The data results are arranged in the form of transcripts, then imported into NVivo 12 software for further analysis. Results: The pickleball community in Jambi is developing the sport through a social and digital approach, with strategies for recruiting members, regular training, tournaments, and promotions via social media, as well as collaboration with other sports communities. Despite limited facilities and support, the community continues to strive to expand its reach and participation. Conclusion: This study revealed that the pickleball community in Jambi developed the sport through regular practice, social media, and tournaments. Despite facing obstacles in facilities and support, the community remained active in introducing the sport. These findings demonstrate the effectiveness of community and digital strategies in expanding the reach of a new sport and open up opportunities for further study on strategy, socio-economic impacts, and stakeholder roles.